The Influence of Competence with the Elements of Knowledge, Understanding, Ability/Skills, Values, Attitudes and Interest on Employee Performance at the Tanjung Perak Port Authority Office in Surabaya - Beni Agus Setiono,; Tri Andjarwati,; Kunto Eko Susilo,; Endah Budiarti,; Pramita Studiviany Soemadijo, (Archives of Business Research, 2021)
The purpose of this study was to test and analyze the influence of competence with elements of knowledge, understanding, abilities/skills, values, attitudes and interests on employee performance at the Tanjung Perak Port Authority Office, Surabaya. This type of research is an associative study that explains the relationship and influence between competency variables on employee performance. The population in this study amounted to 90 people. The sampling technique used the saturated sampling method. Methods of data collection by interview, literature study, observation and questionnaires. The data were analyzed by using the Simple Linear Regression method. This study concluded that competence with indicators of knowledge, understanding, abilities/skills, values, attitudes and interests has a significant effect on improving employee performance at the Tanjung Perak Main Port Authority Office.